2018
DOI: 10.1016/j.jval.2018.09.2516
|View full text |Cite
|
Sign up to set email alerts
|

Pss16 - Cost Per Responder Analysis of Calcipotriol Plus Betamethasone Dipropionate Aerosol Foam Versus Non-Biologic Systemic Therapy in the Treatment of Moderate to Severe Plaque Psoriasis

Abstract: considered (V, 2018). RESULTS: A total of 10,777 patients were estimated to receive biologics or apremilast in the first model year. Increased penetration of apremilast resulted in an estimated reduction of the total budget by 28.6%, leading to costsavings of V31,606,416 over 5 years (V527,470,278 vs V495,863,863). Total costs per patient decreased by V2,374 over the same time period. The model yielded average annual cost-savings of 5.7% compared to the current treatment scenario. The sensitivity analyses conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The potential cost–benefit implications when using Cal/BD foam as a treatment for beyond-mild psoriasis are yet to be determined. It has been suggested that the use of Cal/BD foam as opposed to systemic treatment may result in cost savings [ 24 ]. Given that treatment cost can impact an HCP’s choice of treatment, further insights from real-world experience would help determine the most effective use of Cal/BD foam as a treatment option in this patient segment.…”
Section: Discussionmentioning
confidence: 99%
“…The potential cost–benefit implications when using Cal/BD foam as a treatment for beyond-mild psoriasis are yet to be determined. It has been suggested that the use of Cal/BD foam as opposed to systemic treatment may result in cost savings [ 24 ]. Given that treatment cost can impact an HCP’s choice of treatment, further insights from real-world experience would help determine the most effective use of Cal/BD foam as a treatment option in this patient segment.…”
Section: Discussionmentioning
confidence: 99%